2021
DOI: 10.21608/ejabf.2021.143244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shrimp waste extracted chitin on growth and some biochemical parameters of the Nile tilapia

Abstract: Capture fisheries is the utilization of the usable aquatic organisms by the public with or without permissions (El-Sayed, 2006). Aquaculture is the farming of marine and freshwater organisms under controlled conditions. It is a highly growing food production sector (Ahmed and Thompson, 2019). Its global production of fish in 2018 was approximately 179 million tons (FAO, 2020). Farmed Fish are a chief source of food for poor people (Stead, 2019). It is a cheap form of animal protein (Nölle et al., 2020). Due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Chitin and chitosan supplementation in the diet, indeed, elevates growth rates and feed efficiencies and improves disease resistance in several fish species, including rainbow trout (Oncorhynchus mykiss), Nile tilapia (Oreochromis niloticus), grey mullet (Liza ramada), red sea bream (Pagrus major), Japanese eel (Anguilla japonica), and yellowtail (Seriola quinqueradiata) (Ahmed et al, 2021;Dawood et al, 2020;Elserafy et al, 2021;Kono et al, 1987;Qin et al, 2014;Shi et al, 2020). Despite these positive effects, it is generally accepted that chitin is a limiting factor, constraining the use of insect meals in aquafeeds.…”
Section: Introductionmentioning
confidence: 99%
“…Chitin and chitosan supplementation in the diet, indeed, elevates growth rates and feed efficiencies and improves disease resistance in several fish species, including rainbow trout (Oncorhynchus mykiss), Nile tilapia (Oreochromis niloticus), grey mullet (Liza ramada), red sea bream (Pagrus major), Japanese eel (Anguilla japonica), and yellowtail (Seriola quinqueradiata) (Ahmed et al, 2021;Dawood et al, 2020;Elserafy et al, 2021;Kono et al, 1987;Qin et al, 2014;Shi et al, 2020). Despite these positive effects, it is generally accepted that chitin is a limiting factor, constraining the use of insect meals in aquafeeds.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they provide essential growth factors, vitamins, fatty acids, and amino acids [37]. Several studies have shown that probiotics can be useful in a variety of fish species such as snook, Rohu, red sea bream, Nile tilapia, rainbow trout, catfish, and sea bass [38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…It was confirmed that the growth performance, FCR, and SGR of Nile tilapia decreased as the dietary chitin increased [ 71 ]. Chitin content higher than 10% decreased the growth performance, and up to 5% increased the growth of Nile tilapia [ 72 ]. The other reason might be associated with high calcium and phosphorous levels [ 73 ], which is the case in our control diet as well.…”
Section: Discussionmentioning
confidence: 99%